2015
DOI: 10.4315/0362-028x.jfp-14-248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supercritical Fluid Extraction on the Reduction of Toxic Elements in Fish Oil Compared with Other Extraction Methods

Abstract: High-quality fish oil for human consumption requires low levels of toxic elements. The aim of this study was to compare different oil extraction methods to identify the most efficient method for extracting fish oil of high quality with the least contamination. The methods used in this study were Soxhlet extraction, enzymatic extraction, wet reduction, and supercritical fluid extraction. The results showed that toxic elements in fish oil could be reduced using supercritical C 0 2 at a modest temperature (60°C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…On the other hand, the low oil recovery of PE has been attributed in the past for other fish by‐products to the high water content of the raw material. These studies (Hajeb et al, 2015; Rubio‐Rodríguez et al, 2012) showed higher extraction yields for moisture contents of fish by‐products lower than 20%. In the present case, the low temperature used for PE extraction has also contributed to the low yield.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, the low oil recovery of PE has been attributed in the past for other fish by‐products to the high water content of the raw material. These studies (Hajeb et al, 2015; Rubio‐Rodríguez et al, 2012) showed higher extraction yields for moisture contents of fish by‐products lower than 20%. In the present case, the low temperature used for PE extraction has also contributed to the low yield.…”
Section: Resultsmentioning
confidence: 98%
“…Oils from sturgeon [46,47], common carp [48], striped weakfish [49], jumbo squid [38], sardine [50], orange roughy [38], yellow croaker [51], trout [52], salmon [38,53,54], sardine, and rendered fish meal [55] have been also obtained by SFE over the last decade (Table 1). Reported omega-3 PUFA contents in the extracted oil differ from 0.8 [38] up to 46 %wt [41], depending on the fatty acid profile of the original fish species and the fish part. Studies also showed that omega-3 PUFA content was not affected by the extraction method, since the fatty acid profile of scCO2-extracted fish oil was very similar to that obtained by Soxhlet extraction with hexane [37].…”
Section: Supercritical Fluid Extraction (Sfe) Of Fish Oilmentioning
confidence: 99%
“…for Indian mackerel [41][42][43][44], and 67 g oil/100 g raw material (dry basis) for African catfish [45].…”
Section: Supercritical Fluid Extraction (Sfe) Of Fish Oilmentioning
confidence: 99%
See 2 more Smart Citations